Batata-doce: resistência a nematóides de galhas e caracterização físico-química de clones promissores em betacaroteno - Santos, Adelana Maria Freitas [UNESP] (2015)
Eight sweet potato clones were evaluated regarding the resistance to root-knot nematodes, productivity and physical and physicochemical characteristics. The first experiment was made in greenhouse with experimental design of randomized blocks in 9 x 2 factorial, with eight clones (orange-fleshed BRS Amélia, Beauregard, CNPH 1298, CNPH 1358 and CNPH 1365; white-fleshed Canadense, Uruguaiana and CNPH 1195, one control ('Rutgers' tomato) and two growing seasons (summer and winter) for three root-knot nematode populations: Meloidogyne enterolobii, Meloidogyne incognita and Meloidogyne javanica. The reproduction factor (FR) and the accessions reaction (RA) were evaluated. The second experiment was carried out in field with experimental design of randomized blocks in8 x 2 factorial, with eight clones and two seasons (spring and summer). Total yield(t ha-1), commercial yield (t ha-1), noncommercial yield (t ha-1), length(cm), diameter (cm), mass (g), pH, TA(%), SS (°Brix), ratio, total sugar (%), reducing sugar (%), saccharose (%), starch (%), lipids (%), total protein (%), fiber (%), moisture (%), ash (%), total antioxidant (%), phenolic compounds (mg of gallic acid.100g-1), anthocyanins (mg.100g-1), skin color, flesh color, total carotenoids (mg.100g-1) and betacarotene (mg.100g-1). In the first experiment, the orange fleshed clones CNPH 1298, CNPH 1358 and CNPH 1365 and the white-fleshed clones CNPH 1195, Canadense and Uruguaiana were resistant to M. enterolobii and M. incognita in both seasons. The clone BRS Amélia was only resistant to M. enterolobii and, in a similar way, the clone Beauregard was only resistant to M. incognita in both seasons. Concerning the M. javanica, onlythe orange-fleshed clones (BRS Amélia, Beauregard, CNPH 1195, CNPH 1298, CNPH 1358 and CNPH 1365) showed resistance. In the second experiment on the yield characteristics... (Complete abstract click electronic access below)